Microsporidia infection impacts the host cell's cycle and reduces host cell apoptosis. - Raquel Martín-Hernández; Mariano Higes; Soledad Sagastume; Ángeles Juarranz; Joyce Dias-Almeida; Giles E Budge; Aránzazu Meana; Neil Boonham (PLoS ONE)
Intracellular parasites can alter the cellular machinery of host cells to create a safe haven for their survival. In this regard, microsporidia are obligate intracellular fungal parasites with extremely reduced genomes and hence, they are strongly dependent on their host for energy and resources. To date, there are few studies into host cell manipulation by microsporidia, most of which have focused on morphological aspects. The microsporidia Nosema apis and Nosema ceranae are worldwide parasites of honey bees, infecting their ventricular epithelial cells. In this work, quantitative gene expression and histology were studied to investigate how these two parasites manipulate their host's cells at the molecular level. Both these microsporidia provoke infection-induced regulation of genes involved in apoptosis and the cell cycle. The up-regulation of buffy (which encodes a pro-survival protein) and BIRC5 (belonging to the Inhibitor Apoptosis protein family) was observed after infection, shedding light on the pathways that these pathogens use to inhibit host cell apoptosis. Curiously, different routes related to cell cycle were modified after infection by each microsporidia. In the case of N. apis, cyclin B1, dacapo and E2F2 were up-regulated, whereas only cyclin E was up-regulated by N. ceranae, in both cases promoting the G1/S phase transition. This is the first report describing molecular pathways related to parasite-host interactions that are probably intended to ensure the parasite's survival within the cell.